Perilaku Kristalisasi Polipropilena dengan Penambahan Selulosa Mikrofibril Serat Sorgum sebagai Bio-Based Nucleating Agent - Ismail, Ika; Chalid, Mochamad (SPECTA Journal of Technology, 2017)
Polypropylene with added Microfibrill Cellulosa as additive materials and filler has been investigated. Polypropylene and sorghum fibre has different interface properties, as the result that the compatibility between both are not good. Therefore, modification process for sorghum fibre is needed, the modification process for sorghum surface are alkalinization and bleaching treatment. Alkalinization process is doing with soaking the sorghum fibre in NaOH solution 2% during 2 hours. Bleaching Process used buffer and NaClO2 during 4 hours. Then, polypropylene and microfibrill cellulose mixed with hot melt mixing method. Characterization for this research is how effect from cellulose in sorghum on crystallization of PP. From DSC analysis showed PP with added microfibrill cellulose 1%wt can increase crystallization temperatures up to 126,510C and crstallization time until 8,26 minutes. And the crystallization process may be accelerated 10 seconds.